NEUROPROTECTIVE ACTIVITY OF EXTRACT OF CELERY (APIUM GRAVEOLENS) IN INSILICO STUDY - Mahendra, Reza; Rofik, Ainul; Salim, Hotimah Masdan; Ulfa, Maria; Awwaliyah, Evy Silvia (UNUSA Press, 2021)
Backround: Celery (Apium graveolens L., Apiaceae) is one of the medicinal plants with secondary metabolite components that have pharmacological effects such as vitamin (choline) content. This study aims to evaluate the mechanism and interaction of choline contained in celery on its effectiveness as a neuroprotective. Methods: This research is an experimental research using the in silico study. Results: The insilico search found that the choline content in celery binds to Slc5a7, Chat and Ache. Which has a function in the process of neurotransmitter biosynthesis, neurotransmitter metabolic processes and neurotransmitter secretion processes Conclusion: The celery (Apium graveolens L., Apiaceae) have pharmacological activity as neuroprotective through the interaction of Slc5a7, Chat and Ache